IDENTIFIKASI PERBEDAAN KARAKTERISTIK DOSEN PENELITI DAN PENGAJAR - Lase, Evi Permata Sari; Handaru, Agung Wahyu (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2015)
The aim of this study is to identify the characteristic differences between academic researcher and academic lecturer using an application of multiple discriminant analysis. Results show that there are three characteristics distinguish both of group, that is: 1) searching call for papers/conference/seminar schedules via internet, 2) buying new books with own money, and 3) alocating much more time for doing research rather than teaching. The last finding revealed that 86.4% of observations were correctly classified.